Penguatan Kompetensi Guru Agama Katolik SD-SMP-SMA Se-Paroki Kudus dan Jepara Dalam Implementasi Kurikulum Merdeka - FX.Sugiyana; Andarweni Astuti; Hartutik Hartutik; Nerita Setiyaningtiyas (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This article discusses community service efforts in the context of strengthening Catholic religious teachers in implementing the Independent Curriculum. The focus is to provide Catholic religious teachers with an in-depth understanding of the concepts, principles and values that form the basis of the Merdeka Curriculum. Through a series of trainings, workshops, and mentoring, this article explores how educators can improve teaching skills, integrate Catholic values in learning, and create inclusive environments that support student empowerment. The main emphasis of this article is on follow-up service activities, which involve ongoing mentoring and the formation of learning communities between teachers. By understanding the importance of continuous support, this article creates a picture of how these efforts can strengthen the connection between teachers and the curriculum, shaping education that is responsive to the needs of the times. The results are expected to create a dynamic learning environment, motivate students to develop holistically, and stimulate spiritual and cognitive growth. This article is a contribution to enriching the practice of Catholic religious education, supporting the vision of the Independent Curriculum, and building a bridge between religious values and modern-day needs.